Wild Cultures: A Comparison between Chimpanzee and Human Cultures - Contreras, Diana Rocío Carvajal (Ethnobiology Letters, 2013)
Review of Wild Cultures: A Comparison between Chimpanzee and Human Cultures. Christophe Boesch. 2012. Cambridge University Press. Pp. 276, 68 b & w illustrations, 11 tables. £60 (hardback). ISBN 9781109025370.